Satellite-driven modeling of the upper ocean mixed layer and air-sea co2 flux in the Mediterranean Sea - Taillandier, V.; D'Ortenzio, F.; Antoine, David (ASLO Aquatice Sciences, 2009)
The air-sea CO2 flux, the carbon export to the deep layers, and more generally the carbon budgets are presently poorly characterized in the Mediterranean Sea. A first basin-scale estimation was proposed by D’Ortenzio et al. (2008), using an approach based on an array of unconnected 1D physical-biological-chemical coupled models, massively assimilating satellite information (in particular SeaWiFS ocean color observations). The method was applied to simulate the upper ocean physical and biogeochemical dynamics of the entire Mediterranean Sea over the years 1998 to 2004. In this work, the D’Ortenzio et al. (2008) approach was used to evaluate basin-scale Mediterranean CO2 fluxes for the two periods 1979-1984 and 1998-2004. The rationale here was to feed the 1D model with the CZCS-SeaWiFS coherent data base of ocean color observations presented by Antoine et al. (2005). Comparisons between the two periods on the influence of the physical and biological processes in shaping the pCO2 seasonal evolution will be presented.